Pengaruh Kepemimpinan Kepala Madrasah dan Supervisi Klinis terhadap Kinerja Guru MTs Se-Kabupaten Kebumen - Yakino Yakino (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This research is motivated by the low academic quality of Madrasah Tsanawiyah in Kebumen Regency. One of the causes of low academic quality is due to low teacher performance. To improve teacher performance, the role of the Madrasah Tsanawiyah head, both as a leader and supervisor, is very necessary. The objectives to be achieved through this research are to find out: (1) the influence of the MTs head's leadership on the performance of MTs teachers throughout Kebumen Regency; (2) the effect of clinical supervision on the performance of MTs teachers in Kebumen Regency; and (3) the influence of the leadership of the madrasa head and clinical supervision on the performance of MTs teachers in Kebumen Regency. Data collection using a questionnaire. The population in this study, namely teachers who teach in 88 MTs both public and private, totaling 1,484 teachers. Samples were taken using probability sampling technique or random sampling from 9 MTs. Furthermore, to determine the number of samples, the Herry King Nomogram table was used with a 5% degree of freedom to obtain a sample of 143 respondents. The technique used in analyzing the data through three stages. The three stages are: First, data description. Second, homogeneity and normality tests as prerequisite data before being analyzed. Third, test the hypothesis. The descriptive results showed that the leadership criteria for the head of Madrasah Tsanawiyah in Kebumen Regency were 67.1% very good, 31.5% good, 1.4% good enough, while clinical supervision criteria 7% very good, 39.8% good, 37 .8% sufficient, 14.7% less, and 0.7% not good. The teacher performance criteria are 21% very good, 71.3% good, 6.3% sufficient, and 1.4% less. Through the homogeneity test it is known that the data is not homogeneous because the significance value is 0.000 or less than 0.05. Through the Kolmogorov-Smirnov test it is also known that the data for the principal leadership variable and teacher performance are not normal, while for the clinical supervision variable the distribution is normal. The results of the research analysis show that the probability number is 0.000 or less than 0.05, both the relationship between the leadership of the madrasah head and teacher performance, the relationship between clinical supervision and teacher performance, and the relationship between the leadership of the madrasah head of clinical supervision and teacher performance. This means that there is a significant influence between the leadership relationship of the madrasa head and teacher performance, the relationship between clinical supervision and teacher performance, as well as the relationship between the leadership of the madrasa head and clinical supervision and the performance of Madrasah Tsanawiya teachers.